Randomized, Blinded, Dose-Ranging Trial of an Ebola Virus Glycoprotein Nanoparticle Vaccine With Matrix-M Adjuvant in Healthy Adults. (11th October 2019) - Fries, Louis; Cho, Iksung; Krähling, Verena; Fehling, Sarah K; Strecker, Thomas; Becker, Stephan; Hooper, Jay W; Kwilas, Steven A; Agrawal, Sapeckshita; Wen, Judy; Lewis, Maggie; Fix, Amy; et al.
Abstract: Background: Ebola virus (EBOV) epidemics pose a major public health risk. There currently is no licensed human vaccine against EBOV. The safety and immunogenicity of a recombinant EBOV glycoprotein (GP) nanoparticle vaccine formulated with or without Matrix-M adjuvant were evaluated to support vaccine development. Methods: A phase 1, placebo-controlled, dose-escalation trial was conducted in 230 healthy adults to evaluate 4 EBOV GP antigen doses as single- or 2-dose regimens with or without adjuvant. Safety and immunogenicity were assessed through 1-year postdosing. Results: All EBOV GP vaccine formulations were well tolerated. Receipt of 2 doses of EBOV GP with adjuvant showed a rapid increase in anti-EBOV GP immunoglobulin G titers with peak titers observed on Day 35 representing 498- to 754-fold increases from baseline; no evidence of an antigen dose response was observed. Serum EBOV-neutralizing and binding antibodies using wild-type Zaire EBOV (ZEBOV) or pseudovirion assays were 3- to 9-fold higher among recipients of 2-dose EBOV GP with adjuvant, compared with placebo on Day 35, which persisted through 1 year. Conclusions: Ebola virus GP vaccine with Matrix-M adjuvant is well tolerated and elicits a robust and persistent immune response. These data suggest that further development of this candidate vaccine for prevention of EBOV disease is warranted. Abstract : Ebola GP vaccine was given in 1- or 2-dose regimens, with or without Matrix-M adjuvant. Adjuvanted formulations generated Ebola GP-specific IgG, boosting 10-fold after a second dose. Neutralizing antibodies were detected by 2 assays and remained elevated for 1 year.